Plan estratégico para el Hostal Samana Wasi del cantón Saraguro de la Provincia de Loja - Ordoñez Montaño, Cecilia Maribel (2017)
At present there is living through the country a process of change where the shift government thinks about how by means of the execution of the national plan of the good one to live to guarantee the equitable redistribution of the resources and the wealth all this to the advantage of improving the quality of life of the population. The present work investigativo takes as a purpose to contribute to the development and hotel growth, especially for the Cheap hotel Samana Wasi of the Canton Saraguro, to it, during its development and structure, there apply to themselves all the methods, skills, procedures and the terminology that the modern strategic planeación demands it. Several attainable considered targets appeared, departing from the general who is “to Prepare a strategic plan for the “Cheap hotel Samana Wasi of the canton Saraguro” to strengthen the administrative management and to contribute to the development and sostenibilidad of the company. To know the environment, there was realized an analysis of the PEST and five forces of Porter, for the External Factors and the Internal Factors, there were constructed counterfoils of fortitude, opportunities, weaknesses and threats the counterfoil FODA was applied to determine with major facility the strategic targets, to determine the Mission, Vision, politics, values and the position that has the Cheap hotel in the market. To develop the present investigation the following methods were used: the dialectical method that allowed the comprehension of the diverse phenomena of the nature, of the society and of the thought, by means of the analysis of the history across the time, that is to say how there has been evolving the Cheap hotel, the current situation that will allow to visualize how is life at present the cheap hotel and later to realize a projection to future and to go so far as to have a futurology of the company inside a time space, across the use of this method also one could have access to excellent information about the beginnings and the creation of the Cheap hotel, the inductive method allowed me to determine the grade of acceptance of the Cheap hotel and the current management, the deductive method allowed the compilation of theoretical concepts and to sustain the present work by means of the literature review with precise contents for the development of the investigation. Later the work ends showing that there is proposed a long-term plan for five later years and an operative plan for the first year, and the recommendations do emphasis to the contribution that is realized by means of the incentive on having realized these works and its contribution to the investors, pupils and the society in general.